Chromosome nanoscience and technology - Fukui, Kiichi (CRC Press, 2008)
Reporting results from a six-year Japanese national research project, scientists and engineers illustrate how concepts and techniques from the nano-sciences can further the study of chromosomes, especially aspects of them besides DNA, which has been quite the prima donna for the past few decades. They discuss devices for handling chromosomes, imaging technologies, chromosomes as nano-materials, and informatics.